The Evaluation of Instructor Competency in Informatics - Biser, Natalia G (East Carolina University, 2023)
The use of technology is increasingly prevalent in hospitals, clinics, and other healthcare venues, so nursing programs across the country should integrate it into their curricula by 2022. In 2021, the American Association of Colleges of Nursing (AACN) released new essential core competencies for nursing education, including an expanded informatics domain. Academic integration requires nursing faculty to be competent in technology and informatics to teach the material to students effectively. In addition, the National League of Nursing (NLN) created a vision for nursing education on their changing role in maintaining education about nursing informatics in the class curriculum. However, a common complaint among students and faculty is that nursing faculty are not knowledgeable in nursing informatics. The purpose of this integrative review is to summarize the evidence of the nursing faculty's knowledge, competency, and attitudes regarding the benefit and use of nursing informatics in the baccalaureate programs. Understanding the faculty's knowledge of nursing informatics is the first step in adapting nursing informatics into the curriculum. A review is needed to assimilate evidence-based nursing informatics practice into the classroom. This integrative review was conducted following the PRISMA 2020 guidelines; the level of evidence and quality were analyzed using Joanna Briggs Institute (JBI) Critical Appraisal Tools. A literature search was conducted using the databases Cumulative Index of Nursing and Allied Health Literature (CINAHL), Medline via Pub Med, and ProQuest with the assistance of the University Librarian. Inclusion criteria included articles published in English, international, and academic settings. Exclusion criteria will be articles from nonacademic settings or conference proceedings. The following key terms were utilized during the review of nursing informatics and faculty competency and curriculum: nursing informatics, informatics competency, and nursing faculty. Each article was reviewed for inclusion and exclusion criteria. The review noted three main themes: lack of knowledge in informatics, barriers to implementing the curriculum, and an understanding of nursing informatics. Each theme was analyzed for areas to implement nursing informatics into nursing curricula.
Keywords: Nursing informatics, instructor competency, nursing technology